The Study of spirituality - Jones, Cheslyn; Wainwright, Geoffrey, 1939-; Yarnold, Edward (Oxford University Press, 1986)
A companion volume to The Study of Liturgy, this collection examines the nature and form of individual devotion, discussing the various patterns of Christian discipleship that have evolved through the centuries. Written by contributors representing the Anglican, Roman Catholic, Free Church, and Orthodox traditions, it is the definitive study of spirituality.